2006
DOI: 10.1179/joc.2006.18.5.461
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Epidemiological Characterization of Imipenem-ResistantPseudomonas aeruginosaStrains from a Brazilian Tertiary Hospital: Report from the SENTRY Antimicrobial Surveillance Program

Abstract: The results of this study showed high resistance rates to the majority of antimicrobial agents among P. aeruginosa samples. High imipenem resistance rates were probably due to continuous selection of resistant mutants. The production of MbetaL did not represent a frequent mechanism of carbapenem resistance in this medical center; but a novel MbetaL was identified. Continued antimicrobial surveillance and infection control measures should be emphasized to minimize the emergence and dissemination of antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…Bacterial strains of P. aeruginosa resistant to most antimicrobials and sensitive only to PB have been isolated by clinical microbiology laboratories in most Brazilian hospitals [19,20]; this was corroborated by the results presented in this study. In a study over a period of 1 year in Mexico, P. aeruginosa was the third most frequently isolated species from blood in an intensive care unit (ICU) and the predominant isolate in central venous catheters among the species included in the ESKAPE group of multidrug-resistant microorganisms [21].…”
Section: Discussionsupporting
confidence: 76%
“…Bacterial strains of P. aeruginosa resistant to most antimicrobials and sensitive only to PB have been isolated by clinical microbiology laboratories in most Brazilian hospitals [19,20]; this was corroborated by the results presented in this study. In a study over a period of 1 year in Mexico, P. aeruginosa was the third most frequently isolated species from blood in an intensive care unit (ICU) and the predominant isolate in central venous catheters among the species included in the ESKAPE group of multidrug-resistant microorganisms [21].…”
Section: Discussionsupporting
confidence: 76%
“…9 Data from the Sentry antimicrobial surveillance program documented increases in MDR in Latin America, 10 as have other microbiological studies. [11][12][13][14] Few studies have evaluated hospitals in respect to the epidemiology and trends of overall resistance of MDR GNB. 15 Steady increases of different types of phenomena of multidrug resistance are observed in day-to-day practice in our hospital due to the growing complexity of procedures.…”
Section: Introductionmentioning
confidence: 99%
“…porin mutations and efflux pumps) and/or carbapenem-hydrolyzing β-lactamases, such as metallo-β-lactamases (MβL) 3 . It has been suggested that in the absence of MβL, high imipenem resistance rates in isolates can show great genomic variability, which can be associated with continuous selection of resistant mutants 8 . However, in many geographic regions of Brazil, this has been associated with the dissemination of an epidemic clone that produces SPM MβL 9 .…”
Section: Introductionmentioning
confidence: 99%